Arctic experiment for ICESat/GLAS ground validation with a Micro-Pulse Lidar at Ny-Alesund, Svalbard - Shiobara, Masataka; Yabuki, Masanori; Neuber, Roland; Spinhirne, James D.; Welton, Ellsworth J.; Campbell, James R.; Hart, William D.; Berkoff, Timothy A. (National Institute of Polar Research, 2006)
P(論文) A Micro-Pulse Lidar (MPL) has been operated in Ny-Alesund, Svalbard (78°55'N, 11°56'E, 0.010 km msl) to collect zenith scattering profiles of aerosols and clouds since 1998. The Ice, Cloud, and land Elevation Satellite (ICESat) was launched by NASA in January 2003 with a single payload instrument, the Geoscience Laser Altimeter System (GLAS), designed for active remote sensing of the atmosphere as well as ice sheet height change in the cryosphere. Overpass experiments for ground validation of the ICESat/GLAS atmospheric measurements were performed in 2003 and 2004. Two case-studies comparing lidar measurements from space-borne GLAS and ground-based MPL in the Arctic are described here for a geometrically thick but optically thin cloud and a geometrically thin but optically thick cloud. The result validates the basic procedure for cloud signal processing and attenuation correction of the GLAS data. departmental bulletin paper